Measuring the people fleet: general analysis, interventions and needs. Issue 1 (13th February 2017) - Hesketh, Ian; Cooper, Cary
Abstract : Purpose: The purpose of this paper is to deepen conceptual understanding of how employee wellbeing is identified and categorised in the workplace, and how management information is used to target workplace interventions. Design/methodology/approach: This is a conceptual paper reviewing and discussing contemporary literature and practice, with a focus on themes congruent with employee needs and organisational intervention options in relation to wellbeing. This paper considers wellbeing in the context of police work in the UK, and how a framework can help those charged with leading to understand and act in the interest of both the employee and the organisation. Findings: This paper suggests that the use of an appropriate strategic HR model, such as the General Analysis, Interventions and Needs (GAIN) pyramid (Hesketh and Rhodes, 2015), can assist organisations to develop practical categories and metrics to illustrate employee status in relation to wellbeing. Practical implications: The arguments posed provide opportunities for practitioners to use workforce-modelling tools that assist in identifying, categorising and targeting wellbeing interventions in the workplace. Originality/value: This paper highlights that identifying, categorising and prioritising wellbeing interventions in the workplace has hitherto received little academic attention. This paper contributes by providing a greater practical insight into what may work, which is important for leaders in all organisations, particularly those trying to maintain operational performance whilst undergoing programmes of change.